“To Include or Not to Include?” That is NOT the Question - Barton, Jean M. (Catholic Education: A Journal of Inquiry and Practice, 2000)
Turning to psychological research, intelligence theory, and behavioral studies, this article offers practical advice for implementing an inclusive model of Catholic education. Field-tested models are discussed and suggested components for any inclusion program are provided. The article concludes with a vision statement for inclusive Catholic education.